SKUTKI WADLIWOŚCI CZYNNOŚCI CYWILNOPRAWNEJ W ŚWIETLE USTAWY O PODATKU OD CZYNNOŚCI CYWILNOPRAWNYCH - Radzikowski, Krzysztof (Wydział Prawa i Administracji UAM, 2008)
The paper distinguishes four types of sanctions for defective acts in civil law that have been traditionally described in the civil law literature: (1) (absolute) invalidity of the act, (2) relative invalidity o f the act (challengeability), (3) suspended ineffectiveness of the act in law, and (4) relative ineffectiveness of the act in law. Tax on civil law transactions is not payable in the case of acts in law which have been found absolutely invalid. The collected tax may be recovered on condition that the legal consequences of the statement of will have been waived (relative ineffectiveness). The tax obligation for acts performed under civil law regulations arises only when such an act has been confirmed by a third party. In the absence of a confirmation, the tax obligation will not arise. However, at the time when an act is being performed and it has been found relatively ineffective, the tax obligation holds as provided in general terms and conditions, although it is not bound to be recovered when the effectiveness of the act has been challenged.
CONSEQUENCES OF DEFECTIVE ACTS IN TAX ON CIVIL LAW TRANSACTIONS IN RESPECT OF ACTS REGULATED IN CIVIL LAW